2021
DOI: 10.1021/acs.orglett.1c00399
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Mediated Alkenylation of Alkyl Boronic Acids without an External Lewis Base as an Activator

Abstract: Herein we report a protocol for the direct visible-light-mediated alkenylation of alkyl boronic acids at room temperature without an external Lewis base as an activator, and we propose a mechanism involving benzenesulfinate activation of the alkyl boronic acids. The protocol permits the efficient functionalization of a broad range of cyclic and acyclic primary and secondary alkyl boronic acids with various alkenyl sulfones. We demonstrated its utility by preparing or functionalizing several pharmaceuticals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 49 publications
0
45
1
Order By: Relevance
“…presented a different approach to form alkyl radicals from boronic acids (Scheme 20). [48] In this case, they observed through quenching experiments that benzensulfinates are able to activate boronic acids towards single‐electron oxidation. Following the pathway of a redox‐neutral elimination, the authors found broad applicability of the reaction conditions, that could be applied to variously substituted benzensulfinates and to primary and secondary alkyl boronic acids.…”
Section: Radical Generation Through a Reductive Quenching Cyclementioning
confidence: 99%
“…presented a different approach to form alkyl radicals from boronic acids (Scheme 20). [48] In this case, they observed through quenching experiments that benzensulfinates are able to activate boronic acids towards single‐electron oxidation. Following the pathway of a redox‐neutral elimination, the authors found broad applicability of the reaction conditions, that could be applied to variously substituted benzensulfinates and to primary and secondary alkyl boronic acids.…”
Section: Radical Generation Through a Reductive Quenching Cyclementioning
confidence: 99%
“…Alkyl boronic acids could not efficiently quench excited-state photocatalysts to generate the corresponding alkyl radicals because of their high oxidation potentials ( E red = +2.5 V vs SCE). In 2021, Wang and co-workers overcame this problem by using benzenesulfinate as an alternative Lewis base, which was in situ generated from alkenyl sulfones in the reaction course, to decrease the oxidation potentials of boronic acids (Scheme D) . This protocol permitted the alkenylation reactions of a wide array of boronic acids directly, without the need for the preparation of potassium α-pyrrolidinyltrifluoroborates.…”
Section: Radical-mediated Desulfonylation Of Sulfones Via C–s Bond Cl...mentioning
confidence: 99%
“…The process does not require the presence of an external Lewis base but utilizes the sulfinate anion by reduction of the expelled phenylsulfonyl radical by the reduced form of the photocatalyst (Scheme 13). 46…”
Section: Alkylboron Derivativesmentioning
confidence: 99%